Assessing oral proficiency in computer-assisted foreign language learning: A study in the context of teletandem interactions - Consolo, Douglas Altamiro [UNESP]; Furtoso, Viviane Bagio (FapUNIFESP (SciELO), 2015)
An innovative aspect in the area of language assessment has been to evaluate oral language proficiency in distant interactions by means of computers. In this paper, we present the results of a qualitative research study that aimed at analyzing features of language spoken in a computeraided learning and teaching context, which is constituted by teletandem interactions. The data were collected in the scope of the Teletandem Brazil project by means of interviews, audio and video recordings of online interactions, questionnaires and field notes. The results offer contributions for the areas of assessment, teacher education and teaching Portuguese for foreigners.
Keywords: Assessment; Foreign languages; Synchronous communication; Teletandem